Factors affecting the success of smoking cessation clinic: a cross-sectional study - Ersoy Gölcü, Esra; Çetin, Hüseyin; Tüzün, Sabah; Öner, Can; Şener Cömert, Sevda; Ersin Şimşek, Engin (Journal of Dependence, 2022)
Objective: This study aimed to determine the frequency of smoking cessation and affecting factors in patients who applied to the smoking cessation clinic.Method: This study included smokers aged 18 years and over who applied to the Chest Diseases Clinic Smoking Cessation Outpatient Clinic between 1 April 2019 and 31 July 2019. All participants were evaluated with a sociodemographic questionnaire, Fagerström Test for Nicotine Dependence (FNBT) and Beck Depression Scale during the initial outpatient clinic admission. Subsequently, smoking cessation treatment was started and all participants were called at 6 and 12 months and their smoking cessation status was questioned. Smokers who did never smoked for the last 1 year were accepted as ex-smokers.Results: A total of 270 participants were included in the study, and 48 (19.5%) of the participants were found to quit smoking at the end of one year. There was no significant difference between ex-smokers and current smokers in terms of age, gender, marital status, educational level, employment status, income level, duration of smoking, FNDT and Beck’s depression scores. However, smoking status in the phone call at 6-month was found to be an important factor affecting the success of smoking cessation at 12 months.Conclusion: Although the success rate for individuals who want to quit smoking is quite low in the literature, accessing appropriate pharmacological treatment may increase the success of smoking cessation. Additionally, it has been observed that ex-smokers quit smoking, especially in the first 6 months.
Keywords: Smoking cessation; nicotine dependence; varenicline; tobacco use cessation products